Trends and Insights in Sustainability Accounting in the Public Sector: Unveiling the Research Landscape - Jasni, Nur Syuhada; Kamarudin, Siti Nurhazwani (International Journal of Economics and Financial Issues, 2024)
This study examines the evolution of sustainability accounting in the sector, emphasizing a shift from environmental management to more detailed strategies focusing on environmental preservation, integrating policies and engaging stakeholders. It delves into how policies with public sector activities provide insights into common approaches for measuring and reporting sustainability. By using a combination of bibliometric and thematic analysis, this research analyzes a collection of peer-reviewed papers to identify trends and evolving topics using both quantitative and qualitative methods. The findings indicate a move towards sustainability initiatives, emphasising incorporating technological advancements to enhance sustainability measurement and reporting. Key themes like policy and governance sustainability reporting and the strategic use of technology highlight a trend towards data-driven policymaking and the crucial role of sustainable procurement in the public sector. While comprehensive, the study acknowledges limitations related to database selection and potential publication biases. It emphasizes the importance of research to address gaps and calls, for aligning sustainability reporting standards. This research adds to discussions by providing an overview of sustainability accounting practices within the public sector. It compiles a range of research to offer a comprehension of the subject, setting the stage for upcoming studies and highlighting its importance in academic exploration and real-world use.